Answer:
x = 2
Step-by-step explanation:
Since you need to find x lets make sure to leave that variable in one side of the ecuation so the firts thing you need to do is pass the 6 to the right side of it.
x+4 = 36/6 (notice that 6 passed dividing since it was multiplying (x+4))
After we've done that now we've got that
x + 4 = 6
Now we need to move the "+4" to the right side so we can have only x in the left side.
x = 6 - 4 (notice that the 4 now is being substracted by six, this is determined by the so called "ecuation rules")
So finally we only substract and we get to know that x = 2. So now we can check that its true by replacing its value in the original ecuation.
6(x + 4) = 36
6(2 + 4) = 36
6(6) = 36
36 = 36